A Wideband Differential-Fed Microstrip Patch Antenna Based on Radiation of Three Resonant Modes - Taohua Chen; Yueyun Chen; Rongling Jian (International Journal of Antennas and Propagation)
A wideband differential-fed microstrip patch antenna based on radiation of three resonant modes of TM12, TM30, and slot is proposed in this paper. Firstly, two symmetrical rectangular slots are cut on the radiating patch where the zero-current position of the TM30 mode excites another resonant slot mode. In addition, the slot’s length is enlarged to decrease the frequency of the slot mode with little effect on that of the TM30 mode. To further expand the impedance bandwidth, the width of patch is reduced to increase the frequency of the TM12 mode, while having little influence on that of the TM30 and slot modes. Moreover, a pair of small rectangular strips is adopted on the top of the feeding probes to achieve a good impedance matching. Finally, based on the arrangements above, a broadband microstrip patch antenna with three in-band minima is realized. The results show that the impedance bandwidth (Sdd11<−10 dB) of the proposed antenna is extended to 35.8% at the profile of 0.067 free-space wavelength. Meanwhile, the proposed antenna maintains a stable radiation pattern in the operating band.